PENINGKATAN PERAN WANITA TERHADAP PENANGGULANGAN BENCANA BANJIR DI KAWASAN RAWAN BENCANA BANJIR KABUPATEN SERANG - Mudmainah Vitasari; Fuja Siti Fujiawati (GeoEco, 2018)
Floods are an inevitable event for countries with tropical climates such as Indonesia. Floods can hit anything and everything in the flood-prone areas that allow the emergence of disasters in the form of material losses and casualties. Women who belong to the "vulnerable" do have limitations but with an awareness of their limitations, women who have the potential to make themselves. Women can increase capacity very quickly. The purpose of this research is to formulate Fixed Procedure (PROTAP) from flood disaster for women in disaster-prone area of the flood of Serang regency. This research uses a qualitative descriptive method with simple RnD with sample of the woman in the disaster-prone area of flood of Regency of Serang counted 40 people which randomly. Intake of data with instruments of knowledge, attitude and preparedness. Instruments that can be used as guidance for PROTAP formulation. The result of this research is not yet given the role of woman in disaster management effort which not yet have ability more (disaster capacity). The knowledge needed is knowledge and experience of flood disaster that occurred in Serang prone area of flood. Women's attitude and preparedness will be built on the knowledge of women that have been developed. Attitudes and preparedness can be developed by providing a role in any flood disaster mitigation effort. This research can be certified for everyone in any disaster management effort that can be used in PROTAP that can be used as a guide for women in the effort to overcome the flood disaster in the surrounding environment.Keywords: disaster prone woman, disaster management, flood